Implication of Mitogen-Activated Protein Kinases in T84 Cell Responses to Enteropathogenic Escherichia coli Infection - Czerucka, Dorota (American Society for Microbiology, 2001)
Enteropathogenic Escherichia coli (EPEC) infection of T84 cells induces a decrease in transepithelial resistance, the formation of attaching and effacing (A/E) lesions, and cytokine production. The purpose of this study was to investigate the ability of EPEC to activate mitogen-activated protein (MAP) kinases in T84 cells and to correlate these signaling pathways with EPEC-induced cell responses. T84 cells were infected with either the wild-type (WT) EPEC strain E2348/69 or two mutants, intimin deletion strain CVD206 (ΔeaeA) and type III secretion apparatus mutant strain CVD452 (ΔescN::aphA). Infection of T84 cells with WT but not mutant EPEC strains induced tyrosine phosphorylation of several proteins in T84 cells, including the p46 and p52 Shc isoforms. Kinetics studies revealed that ERK1/2, p38, and c-Jun N-terminal kinase (JNK) MAP kinases were activated in cells infected with strain E2348/69 but not with the mutant strains. Inhibition of MAP kinases with PD98059 or SB203580 did not affect the EPEC-induced decrease in transepithelial resistance or actin accumulation beneath the WT bacteria, but these two inhibitors significantly decreased interleukin-8 (IL-8) synthesis. We demonstrate that EPEC induces activation of ERK1/2, p38, and JNK cascades, which all depend on bacterial adhesion and expression of the bacterial type III secretion system. ERK1/2 and p38 MAP kinases were equally implicated in IL-8 expression but did not participate in A/E lesion formation or transepithelial resistance modification, indicating that the signaling pathways involved in these events are distinct.